Effects of Abelmoschus manihot (L.) and its combination with irbesartan in the treatment of diabetic nephropathy via the gut–kidney axis - Yu, Hongmei; Tang, Haitao; Saxu, Rengui; Song, Yuhui; Cui, Xu; Xu, Jingjing; Li, Nan; Cui, Siyuan; Ge, Haitao; Tang, Wei; Gu, Harvest F. (Frontiers in Pharmacology, 2024)
Background: Clinical observation has recently reported that Abelmoschus manihot (L.), in the form of Huangkui capsule (HKC) and combined with irbesartan (EB) has an effective therapy for type 2 diabetes (T2D) in patients with diabetic nephropathy (DN).The present study aims to explore the mechanisms underlying the treatment of HKC, and its combination with EB in DN via the gut-kidney axis.Methods: HKC, EB, and their combination or vehicle were administered in db/db mice, an animal model for the study of T2D and DN. Comparative analyses of gut microbiota, serum metabolites, and kidney transcriptomics before and after the drug administration were followed.Results: After treatment of HKC, EB and their combination for 4 weeks, UACR in db/db mice with DN was significantly decreased. In gut microbiota, the abundance of Faecalitalea, Blautia, and Streptococcus was increased but Bacteroidetes, Firmicutes, Enterobacteriaceae and Desulfovibrio were decreased. Parallelly, serum metabolites, mainly including Quercetin 3'-glucuronide and L-Dopa, were elevated, while Cortisol and Cytochalasin B were reduced. Furthermore, the S100a8, S100a9, Trem1 and Mmp7 genes in kidneys were downregulated. These altered elements were associated with proteinuria/albuminuria reduction. However, EB had no effects on the changes of blood pressures and specific differentially expressed genes in kidneys.The present study has provided experimental evidence that HKC have effects in regulating the gut-microbiota, circling metabolites, and renal gene activities, which is useful for better understanding the mechanism of A. manihot on the treatment of DN through the gut-kidney axis.